Determinan Kinerja Usaha E-Commerce di Pulau Jawa Masa Pandemi Covid-19 Tahun 2020 - Syahirah, Athaya Salwa; Muchlisoh, Siti (Politeknik Statistika STIS, 2023)
Covid-19 has pushed companies to close their businesses and increased unemployment. Indonesia now has to fight harder to overcome the problems of poverty and unemployment plus health problems. Based on BPS data, Indonesia's TPT in August 2020 increased by 1.84 percent compared to August 2019. Covid-19 also encourages the use of E-Commerce by the community in running their businesses. Businesses that have utilized E-Commerce are still mostly concentrated in Java. This study aims to determine the general description of E-Commerce business performance and the variables that are thought to affect it in Java during the Covid-19 pandemic in 2020 and analyze these variables and their trends. The method used is binary logistic regression analysis. The results show that E-Commerce business owners who are female, belong to Gen Z and Y, started selling online in 2017-2020, have financial statements, use agents, and experience an increase in online sales volume during the Covid-19 pandemic in 2020 have a tendency to experience a greater increase in business performance than E-Commerce businesses with other characteristics.